CHARACTERIZATION OF AFTEEMOON HINDI OR AKASHBEL SOLD IN WHOLESALE MARKET OF HERBAL DRUG AT KHARI BAOLI, DELHI - Siddiquee, MD. RIZWAN AHMAD; SULTANA, AASIA; ASIF, MD (Innovare Journal of Ayurvedic Sciences, 2013)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]--> Objectives: To question reliability of drugs available at wholesale market of crud herbal drug in Delhi by analyzing physiochemical properties of a drug,Â Afteemoon Hindi/ Akashbel. Method: Standardization of crude drug is becoming must for drug industries for GMP, clinical practioners and research works for effective and accurate results. Afteemoon Hindi also called Akashbel is important plant used as drug in Unani and Ayurvedic system of medicine with many bioactive molecules. The drug is used singly and also constitutes important part in various pharmacopeial and patented compound drugs. Study was executed in to characterize the properties of this important drug available in market. Parameters were botanical identification, foreign materials, moisture content/loss on drying, ash values, pH and TLC. Results and conclusion: The parameters show slight variations in results from previously standardized results for the same drug. Therefore it is to conclude that these variations may alter expected outcome of the drug in patient treatment and need to be work out authentication of drug before purchasing. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->